Atopy-Dependent and Independent Immune Responses in the Heightened Severity of Atopics to Respiratory Viral Infections: Rat Model Studies - Lauzon-Joset, Jean-François; Jones, Anya C.; Mincham, Kyle T.; Thomas, Jenny A.; Rosenthal, Louis A.; Bosco, Anthony; Holt, Patrick G.; Strickland, Deborah H. (Frontiers in Immunology, 2018)
Allergic (Th2high immunophenotype) asthmatics have a heightened susceptibility to common respiratory viral infections such as human rhinovirus. Evidence suggests that the innate interferon response is deficient in asthmatic/atopic individuals, whilst other studies show no differences in antiviral response pathways. Unsensitized and OVA-sensitized/challenged Th2high (BN rats) and Th2low immunophenotype (PVG rats) animals were inoculated intranasally with attenuated mengovirus (vMC0). Sensitized animals were exposed/unexposed during the acute viral response phase. Cellular and transcriptomic profiling was performed on bronchoalveolar lavage cells. In unsensitized PVG rats, vMC0 elicits a prototypical antiviral response (neutrophilic airways inflammation, upregulation of Th1/type I interferon-related pathways). In contrast, response to infection in the Th2high BN rats was associated with a radically altered intrinsic host response to respiratory viral infection, characterized by macrophage influx/Th2-associated pathways. In sensitized animals, response to virus infection alone was not altered compared to unsensitized animals. However, allergen exposure of sensitized animals during viral infection unleashes a notably exaggerated airways inflammatory response profile orders of magnitude higher in BN versus PVG rats despite similar viral loads. The coexposure responses in the Th2high BN incorporated type I interferon/Th1, alternative macrophage activation/Th2 and Th17 signatures. Similar factors may underlie the hyper-susceptibility to infection-associated airways inflammation characteristic of the human Th2high immunophenotype.